Tissue Culture and Light Elicitor Enhancing Secondary Metabolite on Jasmine - Dwie Retna Suryaningsih; Indarwati Indarwati; Jajuk Herawati (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
Jasmine is a commercially ornamental flower crop cultivated plant that is highly valued for producing jasmine essential oil as a secondary metabolite. Essential oil is extracted from jasmine, which is in great demand in the perfumery, flavor, and food additives industry. Plant tissue culture technologies could be authorized by regular sterile conditions from explants for the way for secondary metabolite multiplication. This study aims to investigate the effects of callus formation and photoperiod on the quality, quantity, and secondary metabolites of jasmine through tissue culture. The method used in this study was a completely randomized factorial design with callus formation and photoperiod. The result showed that the callus formation and photoperiod did not influence the callus quality obtained from profiling. Callus quality observation revealed the best result on a three-month-old callus and 12 hours of the light period (1.86). Furthermore, the secondary metabolite of the callus highlighted that a one-month-old callus and 6 hours of the light period produce the highest Jasmone level of 0.17%.